WHEN IT COMES TO EAST: REFLECTIONS ON TRANSFERRING THE PRINCIPLES AND PRACTICE OF RECOVERING-CITIZENSHIP TO HONG KONG - Fang, Fan; Fung, Kaitlyn (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2021)
The community psychiatric service in Hong Kong started after a mass murder by a man with severe mental illness (SMI). Fear-based stigmatization remains common in the community. Although recovery-oriented care gradually takes root in Hong Kong, it flourishes mainly within the mental health sector. People with SMI remain isolated from the rest of the residents. Recovering-citizenship might help fill the service gap and facilitate a true social inclusion of people with SMI in the community. However, we need to pay attention to several possible challenges when adapting the recovery citizenship concept in Hong Kong. First, citizenship is a complex concept for people in Hong Kong. Second, the New Public Management (NPM) regime adopted in the social welfare sector significantly impacted the services for people with SMI. Third, traditionally, “Face Concern” is a potential cultural barrier for people with SMI and their families to connect to society fully. In respect of these challenges, implementing qualitative and quantitative research to capture the exact meaning of citizenship to Hong Kong people is the first essential step in putting this theoretical framework into practice. Meanwhile, we should bear in mind that recovering citizenship should be promoted in the whole community with the assistance of peer support staff instead of only in the mental health community. Last but not least, the recovering citizenship activities should also include the family of the people with SMI rather than solely targeting the individuals.